Describe mathematical creative thinking skills and problem-solving strategies by prospective teacher students on non-routine problems - Heru Kurniawan; Prastyo Budi Darmono; M Mursalin; Yilun Shang; Robert Weinhandl; Rajinder Sharm (SAINTIS Publishing, 2022)
This study aims to investigate and describe how creative thinking skills and problem-solving strategies are used by prospective mathematics teacher students in solving non-routine problems. Non-routine problems given to the subject require the use of mathematical conceptual understanding and procedural knowledge or algorithms used to find solutions to solve them. The results of the analysis of student-teacher solutions show that each student uses at least two problem-solving strategies. The most frequently used strategies are using algebraic manipulation, making logical reasoning with diagrams/models, and trial and error. Students with high categories show proficiency in using appropriate problem-solving strategies and students with lower categories still show an introduction to solving strategies so that they are confused about choosing the right strategy for a particular problem.